Exploring the biological mechanisms of severe COVID-19 in the elderly: Insights from an aged mouse model - Ma, Li; Lin, Xian; Xu, Meng; Ke, Xianliang; Liu, Di; Chen, Quanjiao (Virulence, 2025)
The elderly population, who have increased susceptibility to severe outcomes, have been particularly impacted by the coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), leading to a global health crisis. However, definitive parameters or mechanisms underlying the severity of COVID-19 in elderly people remain unclear. Thus, this study seeks to elucidate the mechanism behind the increased vulnerability of elderly individuals to severe COVID-19. We employed an aged mouse model with a mouse-adapted SARS-CoV-2 strain to mimic the severe symptoms observed in elderly patients with COVID-19. Comprehensive analyses of the whole lung were performed using transcriptome and proteome sequencing, comparing data from aged and young mice. For transcriptome analysis, bulk RNA sequencing was conducted using an Illumina sequencing platform. Proteomic analysis was performed using mass spectrometry following protein extraction, digestion, and peptide labelling. We analysed the transcriptome and proteome profiles of young and aged mice and discovered that aged mice exhibited elevated baseline levels of inflammation and tissue damage repair. After SARS-CoV-2 infection, aged mice showed increased antiviral and inflammatory responses; however, these responses were weaker than those in young mice, with significant complement and coagulation cascade responses. In summary, our study demonstrates that the increased vulnerability of the elderly to severe COVID-19 may be attributed to an attenuated antiviral response and the overactivation of complement and coagulation cascades. Future research on antiviral and inflammatory responses is likely to yield treatments that reduce the severity of viral respiratory diseases in the elderly.